Between Parenting Styles and Difficult Eating Behavior - Astika Dwi Yanti; Dona Sartika (Jurnal Keperawatan Profesional (KEPO), 2026)
Feeding difficulties among preschool children can interfere with nutritional intake and negatively impact their growth and development. Parenting style plays a crucial role in shaping children’s eating behaviors because parents determined food choices, feeding practices and the eating environment experienced by the child. This study aimed to identify the relationship between parenting style and feeding difficulties among preschool children in the working area of Bambu Apus Community Health Center in South Tangerang City. A quantitative approach with a cross-sectional design was used, involving 186 respondents selected through purposive sampling. Data were collected using structured questionnaire on parenting style and feeding behavior. Data were analyzed using univariate and bivariate methods with Spearman Rank correlation testing. The results demonstrated a significant relationship between parenting style and feeding difficulties among preschool children. In conclusion, parenting styles are related to children’s feeding difficulties behavior. It was recommended that parents apply supportive parenting practices to build healthy eating habits and that health workers enhance education regarding appropriate feeding practices for preschool children.